2008
DOI: 10.1074/jbc.m704724200
|View full text |Cite
|
Sign up to set email alerts
|

BMP-2 Induces Osterix Expression through Up-regulation of Dlx5 and Its Phosphorylation by p38

Abstract: Osterix, a zinc-finger transcription factor, is specifically expressed in osteoblasts and osteocytes of all developing bones. Because no bone formation occurs in Osterix null mice, Osterix is thought to be an essential regulator of osteoblast differentiation. We report that bone morphogenetic protein-2 (BMP-2) induces an increase in Osterix expression, which is mediated through a homeodomain sequence located in the proximal region of the Osterix promoter. Our results demonstrate that induction of Dlx5 by BMP-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
187
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(200 citation statements)
references
References 54 publications
10
187
0
3
Order By: Relevance
“…Mid-and late-stage osteogenic markers including OPN, bone sialoprotein (BSP), and OCN are temporal successors to RUNX2 and OSX expression after rhBMP-2 stimulation [63]. The complex temporal expression profiles of OPN, BSP, and OCN have been elucidated [15,16,23,25,26,30,53,59,66]; therefore, a coordinated, temporal RNAi treatment cycle may enhance the duration and intensity of gene silencing and prevent HA deposition in vitro. Consequently, the evolution of RNAi therapeutics must match RNAi targets to their expression profiles.…”
Section: Discussionmentioning
confidence: 99%
“…Mid-and late-stage osteogenic markers including OPN, bone sialoprotein (BSP), and OCN are temporal successors to RUNX2 and OSX expression after rhBMP-2 stimulation [63]. The complex temporal expression profiles of OPN, BSP, and OCN have been elucidated [15,16,23,25,26,30,53,59,66]; therefore, a coordinated, temporal RNAi treatment cycle may enhance the duration and intensity of gene silencing and prevent HA deposition in vitro. Consequently, the evolution of RNAi therapeutics must match RNAi targets to their expression profiles.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, several reports have also indicated that the p38 pathway regulates the expression and activation of critical transcription factors implicated in osteoblastogenesis, i.e., Dlx5, Runx2, and Osx [5,[10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…11,12 Dlx5, a homeodomain transcription factor, is responsive to osteogenic signals from BMP-2 and mediates the expression of Runx2 and osterix. 13,[16][17][18][19] b-Catenin, when allowed to accumulate intracellularly in response to canonical Wnt signaling, combines with the transcriptional elements TCF and LEF and activates Runx2 expression. 11,24,25 PMMA particles could inhibit the expression of these transcription factors by disrupting upstream signaling pathways, receptor-matrix interactions, or cellular synthesis and transport mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 Dlx5 is a homeobox domain transcription factor that also regulates osteogenesis [13][14][15] and is involved in the response of osteogenic cells to BMP-2. [16][17][18] Msx2, another homeodomain transcription factor, is a functional antagonist and repressor of Dlx5-induced osteogenesis. [19][20][21][22][23] b-Catenin, a transcriptional activator of the canonical Wnt signaling pathway, associates with the DNA-binding proteins TCF and LEF, and stimulates Runx2 transcription.…”
mentioning
confidence: 99%